2013
DOI: 10.4049/jimmunol.1300041
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Defective Follicular Exclusion of Apoptotic Antigens Due to Marginal Zone Macrophage Defects in Autoimmune BXD2 Mice

Abstract: Marginal zone macrophages (MZMs) act as a barrier to entry of circulating apoptotic debris into the follicles of secondary lymphoid organs. In autoimmune BXD2 mice, there is a progressive reduction in the function and numbers of MZMs. Absence of MZMs results in retention of apoptotic cell debris within the MZ and increased loading of apoptotic cell antigens on MZ B cells and MZ-precursor (MZ-P) B cells. The MZ-P B cells are capable of translocating the apoptotic cell antigens to the follicular zone and stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…A common feature of SLE in both human and mouse models of SLE is decreased clearance of ACs and increased production of type I IFNs by pDCs (1-3, 6, 9-11, 13, 14, 39). We and others have previously shown that physical deletion or spontaneous loss of MARCO + MZMs resulted in defective AC clearance (2, 12-15, 40, 41) and that such a defect is associated with the development of lupus in susceptible mouse models (2,42). We analyzed the distribution of MARCO + cells in the spleens of non-SLE controls (n = 6) and in the spleens pf patients with SLE (n = 5) and found a dense layer of MARCO + cells in the perifollicular regions in all non-lupus control spleens; however, this layer of MARCO + cells was significantly reduced in all SLE spleens ( Figure 1A).…”
Section: Decreased Marcomentioning
confidence: 94%
See 4 more Smart Citations
“…A common feature of SLE in both human and mouse models of SLE is decreased clearance of ACs and increased production of type I IFNs by pDCs (1-3, 6, 9-11, 13, 14, 39). We and others have previously shown that physical deletion or spontaneous loss of MARCO + MZMs resulted in defective AC clearance (2, 12-15, 40, 41) and that such a defect is associated with the development of lupus in susceptible mouse models (2,42). We analyzed the distribution of MARCO + cells in the spleens of non-SLE controls (n = 6) and in the spleens pf patients with SLE (n = 5) and found a dense layer of MARCO + cells in the perifollicular regions in all non-lupus control spleens; however, this layer of MARCO + cells was significantly reduced in all SLE spleens ( Figure 1A).…”
Section: Decreased Marcomentioning
confidence: 94%
“…Systemic lupus erythematosus (SLE) and mouse models of lupus both exhibit a central feature of increased circulating apoptotic cell autoantigens (AC-Ags) and, in most cases, elevated type I IFN signaling produced by plasmacytoid DCs (pDCs) (1)(2)(3). The most accepted model is that the presence of uncleared ACs or AC-autoantibody immune complexes with DNA-or RNA-containing immune components can signal production of type I IFNs by pDCs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations